Failure mode and effects analysis and sensitivity analysis for a neutral point re-injection multi-pulse voltage source converter - A. Valderrabano-Gonzalez; H.R. Robles-Campos; F. Beltran-Carbajal; R. Tapia-Olvera; J.C. Rosas-Caro; O. Aguilar-Mejia (e-Prime: Advances in Electrical Engineering, Electronics and Energy, 2025)
Sensitivity Analysis plays a crucial role in the design, control, and optimization of multi-pulse Voltage Source Converters. It helps engineers assess how variations in parameters influence system performance, enabling the development of more efficient and robust converters. This study presents some Failure Modes and Effects Analysis that intends to identify the most affected components when a gate disconnection failure occurs, making them critical points for stress management. Additionally, the most vulnerable components when gates remain connected to high value are distinguished. Verifying the voltage output shape, it can be noticed that RMS voltage measurements are not a reliable indicator for tracking failure, whereas THD offers a more effective solution. Understanding these failure modes is essential for refining the design and control strategies of electronic converters, particularly in applications such as motor control and StatCom. Sensitivity analysis also strengthens control algorithms, ensuring that they can effectively accommodate parameter fluctuations while aiding in fault diagnosis and failure prediction.The early detection of switch malfunctions in power converters is essential for maintaining system reliability, safety, performance, and cost efficiency. Timely identification allows for proactive maintenance, preventing extensive damage and ensuring continuous operation. As the converters become increasingly integral to various applications, implementing reliable fault detection mechanisms is essential for sustaining their optimal performance and long-term functionality.